Ethnoscience in Physics Learning: A Systematic Literature Review - Kasim, Muliyani; Jumadi, Jumadi; Mundilarto, Mundilarto (STKIP Singkawang, 2025)
This article presents a systematic review of ethnoscience in physics learning. This research was conducted to examine how the utilization of ethnoscience in physics learning. This type of research is a Systematic Literature Review (SLR) with the PRISMA method. Findings on google scholar found 30 articles that match the theme. Ethnoscience obtained from the results of this review include traditional games, traditional foods and drinks, dances, musical instruments, crafts, history of a region, and habits carried out by residents to meet their needs. Utilization of various kinds of ethnoscience in physics learning can produce products in the form of learning media such as modules, learning comics, booklets, and also other learning media developed by utilizing technology. In addition to learning media, ethnoscience-based learning tools were also found. These learning tools include Learning Implementation Plans (RPP), Learner Worksheets (LKS), and assessment instruments. Ethnoscience in learning can also be integrated with learning models. Learning physics by utilizing ethnoscience can influence learning outcomes, critical thinking skills, concept understanding, learning motivation, interest, science literacy, and student character.